50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-423
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of Time Spectral Methods for Practical Rotorcraft Problems

Abstract: For flows with strong periodic content, time-spectral methods can be used to obtain time-accurate solutions at substantially reduced cost compared to traditional time-implicit methods which operate directly in the time domain. In their original form, time spectral methods are applicable only to purely periodic problems and formulated for single grid systems. A wide class of problems involve quasi-periodic flows, such as maneuvering rotorcraft problems, where a slow transient is superimposed over a more rapid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Overset solvers typically employ a spatial smoothing operation to populate the solution within hole cuts with non zero data in case such points are inadvertently queried. Mavriplis et al [15] outlined a general Time-Spectral solver for relative motion by taking advantage of this common feature. In this approach, Laplace's equation is solved over the domain of blanked spatial nodes using the data on the hole cut fringe as the boundary condition.…”
Section: Dynamic Hole Cutting and The Hybrid Time-spectral Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overset solvers typically employ a spatial smoothing operation to populate the solution within hole cuts with non zero data in case such points are inadvertently queried. Mavriplis et al [15] outlined a general Time-Spectral solver for relative motion by taking advantage of this common feature. In this approach, Laplace's equation is solved over the domain of blanked spatial nodes using the data on the hole cut fringe as the boundary condition.…”
Section: Dynamic Hole Cutting and The Hybrid Time-spectral Methodsmentioning
confidence: 99%
“…These approaches prove worthy for simple configurations but are not general solutions for the case of arbitrary relative motion. Mavriplis et al [15] demonstrated a general approach to treat dynamically-blanked nodes by applying Laplacian smoothing to populate blanked data using the solution on the boundaries of hole cuts. In the current work, a hybrid Time-Spectral scheme capable of consistently treating dynamically-blanked nodes resulting from general relative motion between overset grids is developed and implemented within NASA's OVERFLOW solver.…”
mentioning
confidence: 99%
“…Therefore, the effect of nonlinear harmonic coupling would not be considered. On the other hand, in the nonlinear harmonic method, known as Harmonic Balance , 13,15,16 Non-Linear Frequency Domain (NLFD), 29,30,34,35 and Time Spectral, 5,6,11,12,26,27,44,53 all the harmonic equations are solved coupled. Besides, there is no restriction on the amplitude of the perturbation terms.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to fill the blanked nodes with solution data via spatial averaging and proceed with the standard Time-Spectral method (cf. [17]). While attractive for its simplicity, this approach is inconsistent.…”
Section: mentioning
confidence: 99%